2017
DOI: 10.1039/c7ra02575k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of silver-anchored polyaniline–chitosan magnetic nanocomposite: a smart system for catalysis

Abstract: A novel and smart four component system composed of chitosan, polyaniline, magnetite and silver was exploited for catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 66 publications
2
29
0
Order By: Relevance
“…Great efforts have been devoted toward the preparation of CP nanomaterials for the fabrication of miniaturized novel flexible sensor platforms that enable portability and high-density arrays because of using small sample amounts, which offer excellent prospects in sensor nanotechnology for advanced detection systems [21]. Recent studies have demonstrated the synthesis of nanostructured CPs with controlled shape and size, which ranged from lithographic techniques to chemical methods [22][23][24][25][26][27][28][29][30][31][32][33]. Stejskal and coworkers demonstrated synthesizing PANI nanostructures and its derivatives by the chemical oxidative polymerization in water [34][35][36].…”
Section: Synthesis Of Nanostructured Conducting Polymersmentioning
confidence: 99%
“…Great efforts have been devoted toward the preparation of CP nanomaterials for the fabrication of miniaturized novel flexible sensor platforms that enable portability and high-density arrays because of using small sample amounts, which offer excellent prospects in sensor nanotechnology for advanced detection systems [21]. Recent studies have demonstrated the synthesis of nanostructured CPs with controlled shape and size, which ranged from lithographic techniques to chemical methods [22][23][24][25][26][27][28][29][30][31][32][33]. Stejskal and coworkers demonstrated synthesizing PANI nanostructures and its derivatives by the chemical oxidative polymerization in water [34][35][36].…”
Section: Synthesis Of Nanostructured Conducting Polymersmentioning
confidence: 99%
“…Aerward, 0.5 mL of freshly prepared NaBH 4 solution (10 mg mL À1 ) was added to the previous solution, then the reduction progress was monitored via the measurement of the absorption spectra over time. 31…”
Section: Catalytic Activity Of Mtps Nanocompositementioning
confidence: 99%
“…Further, anchoring metal NPs into mesostructured materials realizes a promising catalytic activity, while the stability and reusability of the non-supported NPs are the major drawbacks [26]. In order to overcome this problem, efforts have been devoted toward anchoring metal NPs in solid supports, especially nanostructured solid support such as mesoporous silica and nanostructured polymer to realize composite catalysts having high performances without affecting the overall catalytic activity of individual metal NPs [27][28][29].…”
Section: Introductionmentioning
confidence: 99%